Influencer Marketing and Consumer Behaviour: A Systematic Literature Review - Aswathi Kanaveedu; Jacob Joseph Kalapurackal
Influencer marketing is an emerging area in the field of marketing. Specifically, this topic grabs the attention of several academicians and practitioners because of the key role played by influencers to stimulate consumer behaviour. Significantly, a systematic way of analysing and summarising the works of literature in this nascent area is necessary. A systematic literature review provides a comprehensive overview of the whole literature studied. From this knowledge, a systematic literature review has been undertaken from the period of 2016 to 2021 based on 65 articles from the ABDC journal to fetch relevant research themes, methodology, theories, variables, antecedents and consequences and potential research gaps. From this information, this research proposed an integrative framework which depicts the role of social media influencers in activating consumer behaviour. Future research direction has presented comprising of knowledge gap in the existing literature from key areas such as theory, methodology and settings. This research provides implications for both theories and practice.